THE INFLUENCE OF INTERPERSONAL AND MARKETING COMMUNICATION ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION - Christover, William (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study examines the influence of interpersonal communication and marketing communication on customer loyalty, mediated by customer satisfaction. The research focuses on customers of BCA KCU Pontianak Bank, utilizing primary data collected through online questionnaires. SEM-PLS was employed for data analysis. Key findings reveal that: (1) interpersonal communication has a significant positive impact on customer satisfaction; (2) marketing communication does not exert a significant influence on customer satisfaction; (3) interpersonal communication, marketing communication, and customer satisfaction collectively demonstrate a significant positive effect on customer loyalty; (4) customer satisfaction effectively mediates the relationship between interpersonal communication and customer loyalty; and (5) customer satisfaction fails to mediate the influence of interpersonal communication on customer loyalty.